Till death do us part: football as part of everyday life amongst Dynamos Football Club fans in Zimbabwe. Issue 2 (2nd April 2016) - Chiweshe, Manase Kudzai
Abstract: This paper demonstrates the nexus between social identity and supporting a soccer team. It highlights that there are deeper underlying meanings and assumptions to one's support of a sporting team. From the intense regional rivalry that characterized medieval ball games to the national, religious, ethnic and political antagonisms that are present in modern day football, we can highlight the continued role of football in the processes of identity construction and maintenance. I explore how fan identities are formed and how they mediate in fans' social lives. Supporters of Dynamos Football Club in Zimbabwe offer a good example of how fans form indispensable attachments to clubs. Lived experiences of these fans show that supporting a football team is more than just going to the stadium, rather it transcends one's social being. Being a fan is an important part of one's social identity and affects most aspects of one's life. There is something more to supporting a football team besides entertainment. Supporting a football team is a kind of marriage, a commitment similar to 'till death do us part'.